Enhancement of Tumor Cell Death by Combining gef Gene Mediated Therapy and New 1,4-Benzoxazepin-2,6-Dichloropurine Derivatives in Breast Cancer Cells - Ramírez, Alberto; Conejo-García, Ana; Griñán-Lisón, Carmen; López-Cara, Luisa C.; Jiménez, Gema; Campos, Joaquín M.; Marchal, Juan A.; Boulaiz, Houria (Frontiers in Pharmacology, 2018)
New treatment modalities are urgently needed to better manage advanced breast cancer. Combination therapies are usually more effective than monotherapy. In this context, the use of cyclic and acyclic O,N-acetals derivative compounds in combination with the suicide gef gene shown a potent anti-tumour activity and represent a new generation of anticancer agents. Here, we evaluate the use of the gef gene to promote and increase the anti-tumour effect of cyclic and acyclic O,N-acetals purine derivatives and elucidate their mechanisms of action. Among all compounds tested, those with a nitro group and a cyclic pattern structures (FC-30b2, FC-29c and bozepinib) are the most benefited from the gef gene effect. These compounds, in combination with gef gene, were able to abolish tumour cell proliferation with a minimal dose leading to more effective and less toxic chemotherapy. The effect of this combined therapy is triggered by apoptosis induction which can be found deregulated in the later stage of breast cancer. Moreover, the combined therapy leads to an increase of cell post-apoptotic secondary necrosis that is able to promote the immunogenicity of cancer cells leading to a successful treatment. This data suggests that this novel combination therapy represents a promising candidate for breast cancer treatment.